A Study the Characteristics of Bifidobacterium ssp Isolated from Breast Milk as a Probiotic in Vitro (Eurasian Medical Research Periodical, 2022)
Probiotics as live supplements or living microorganisms that, when consumed, can provide health advantages beyond basic nutrition and can also improve the host's gut microbial balance. The objective of the present study was to recognize Bifidobacterium isolates from breast milk as a potential probiotic. A total of 60 out of 90 samples (66.67%) reveal positive results collected from human breast milk at Al-Zahra teaching and Al-kut Hospital, Wasit province in Iraq by biochemical test. 30 positive samples for Bifidobacterium isolates were identified by PCR (16S rRNA sequencing), study the tolerance of Bifidobacterium isolates in simulated gastric juice, and antimicrobial activity against pathogenic bacteria (Escherichia coli and Staphylococcus aureus) by using the well diffusion method. Bifidobacterium isolates showed the ability to tolerance of simulated gastric juice. There were significant differences (P ≤ 0.05) among the average of viable cells count of Bifidobacterium in thirty samples, where it decreased from 5.430 log CFU ⁄ mL at zero time (before the incubation time) at pH 2.3 to 4.908 log CFU ⁄ mL after an incubation period (after 3 hours) at 37º C and pH (2.3). Moreover, the isolated bacteria have antimicrobial effects against S. aureus and E. coli. Bifidobacterium isolates showed a higher of antimicrobial activity against Gram positive bacteria (S. aureus) than Gram negative bacteria (E. coli). Bifidobacterium isolated exhibited support properties as probiotic, consequently, the importance of breast-feeding compared to bottle-feeding is shown.